Examining an Irregularly Sampled Time Series for Whiteness (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Suppose it is of interest whether the series itself is white noise. The empirical Fourier transform is proposed to address this question.